Analisis Peran Lingkungan Sosial Terhadap Minat Peserta Didik dalam Memilih Pendidikan Tinggi - Rif’atul Makhrisa; Sugeng Pradikto (Jurnal Kajian dan Penelitian Umum, 2025)
This study analyzes the role of social environment on students' interest in choosing higher education using a qualitative approach based on secondary data. Factors influencing students' decisions to continue higher education involve various dimensions, including family support, peer influence, government policy, and technological developments. The family plays an important role in providing encouragement or obstacles, depending on the educational background of the parents. Peers also have a major influence in shaping students' views on the importance of higher education. In addition, social media and technology provide wider access to information, although it can create gaps if not balanced with adequate digital literacy. Technological changes and the development of skills-based industries encourage students' interest in choosing more applicable higher education paths, while government policies such as tuition subsidies and scholarships can increase access for students from low-income economic backgrounds. However, socio-economic inequality and uneven technological infrastructure are challenges in creating equal access for all levels of society. This study highlights the importance of inclusive policies, adaptation of universities to labor market needs, and broader counseling for families and students in order to make better decisions about higher education. The results of this study are expected to provide insight into the development of more sustainable and equitable education policies across all levels of society.